2005
DOI: 10.1007/s10194-005-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

Migraine aura without headache compared to migraine with aura in patients with affective disorders

Abstract: The characteristics of psychiatric comorbidity in migraine have been studied in migraine with aura (MA) and migraine without aura (MO). Little information is available concerning patients with migraine aura without headache. In a study of 201 patients with major affective disorders (DSM–IV) we have described the clinical characteristics of patients with these three sub–types of migraine (IHS criteria) and compared the MA and migraine aura without headache groups. Compared to patients having MA ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Compared with men, women often receive a diagnosis of both migraine (24 vs. 9%) and major depression (24 vs. 13%) by age 30, with the relative female risk increasing for migraine in late adolescence and for major depression after about age 20 [32]. MA is strongly associated with an early age of onset (OR 11.4, age \ 15 years, OR 5.6, age 15-24 years), and this variable explains the difference between the two migraine groups (MA vs. migraine aura without headache) better than the variables of suicide attempt (OR 3.2, p = 0.13, NS) or affective temperament (OR 4.0, P = 0.047) [33]. Migraine onset was earlier than mood disorder onset, and Franchini et al [34] found no difference in migraine distribution according to the polarity of mood disorder.…”
Section: Psychiatric Comorbiditymentioning
confidence: 88%
“…Compared with men, women often receive a diagnosis of both migraine (24 vs. 9%) and major depression (24 vs. 13%) by age 30, with the relative female risk increasing for migraine in late adolescence and for major depression after about age 20 [32]. MA is strongly associated with an early age of onset (OR 11.4, age \ 15 years, OR 5.6, age 15-24 years), and this variable explains the difference between the two migraine groups (MA vs. migraine aura without headache) better than the variables of suicide attempt (OR 3.2, p = 0.13, NS) or affective temperament (OR 4.0, P = 0.047) [33]. Migraine onset was earlier than mood disorder onset, and Franchini et al [34] found no difference in migraine distribution according to the polarity of mood disorder.…”
Section: Psychiatric Comorbiditymentioning
confidence: 88%
“…MA is strongly associated with an early age of onset (OR: 11.4, age <15 years, OR: 5.6, age 15–24 years), and this variable explains the difference between the two migraine groups (migraine aura versus migraine aura without headache) better than the variables of suicide attempt (OR: 3.2, P = 0.13, NS) or affective temperament (OR: 4.0, P = 0.047) 44. Migraine onset was earlier than mood disorder onset, and Franchini et al found no difference in migraine distribution according to the polarity of mood disorder,41 consistent with the findings of a previous study 51…”
Section: Epidemiologymentioning
confidence: 98%
“…Studying the relationship between subtypes of migraine headaches and affective disorders may be a way to explore further a possible common pathomechanism in both disorders 44. Disturbances in serotonergic systems are found in completed and attempted suicides,45 and the serotonergic systems are involved in the pathophysiology of both migraine and affective disorders 46,47…”
Section: Pathophysiologic Basesmentioning
confidence: 99%
See 2 more Smart Citations